The Development and Evaluation of a Therapeutic Playgroup for Children with Developmental Delay - Armstrong, Jodie Jeannette (Curtin University, 2019)
Jodie’s consumer driven doctorate entitled ‘The development and evaluation of a therapeutic playgroup for children with developmental delay’ arose from parents’ desire for early access to therapy and connection with other families sharing their experience when first referred for services. Embedded into the Child Development Service, this seven-stage doctorate collaborated with over 150 consumers, policy-makers, practitioners and community members during the planning, development, and evaluation, ensuring translation and the development of an intervention of relevance.